Teologi Pemulihan dan Kesempatan Kedua dalam Perspektif Biblika: Analisis Naratif Kisah Yohanes Markus dan Implikasinya bagi Spiritualitas Kristen - Beni Chandra Purba (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2026)
Failure in Christian ministry is often perceived as the end of one's calling, creating a need for a theological understanding of restoration and second chances. This study aims to analyze the theological meaning of failure and restoration in the story of John Mark and its implications for Christian spirituality. The study employs a qualitative method through literature review and narrative analysis of Acts 12-15, Colossians 4:10, Philemon 1:24, and 2 Timothy 4:11. The findings reveal that John Mark experienced a transformation from failure to restoration and was eventually entrusted again with ministry responsibilities. This process occurred through God's grace manifested in Barnabas's mentorship, character formation, reconciliation, and the support of the faith community. The study concludes that failure does not bring an end to a person's calling; rather, it can become a means of spiritual growth and ministerial restoration. The novelty of this study lies in its integration of the concepts of failure, second chance, reconciliation, and renewed involvement in ministry, resulting in the concept of a spirituality of second chances as a paradigm for contemporary Christian faith formation and leadership.